Fare, osservare o punire. L’importanza della disgiuntiva (Società e diritti, 2020)
Abstract: The author presents his reflections on the repercussions on the penal system and the consolidated legal concepts in this area, developing the observations proposed during the study day dedicated to the "covid emergency between law and criminal trial" organised by the DiP LaP of the University of Verona.
Keywords: Keywords: Criminal Law; Pandemic Emergency; Individual Rights.